2016
DOI: 10.1002/bem.21953
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role of pulsed electromagnetic fields in management of patellofemoral pain syndrome? Randomized controlled study at one year follow‐up

Abstract: Patellofemoral pain syndrome (PFPS) is a common cause of recurrent or chronic knee pain in young adults, generally located in the retropatellar region. Etiology is controversial and includes several factors, such as anatomical defects, muscular imbalance, or joint overuse. Good results have been reported with exercise therapy, including home exercise program (HEP). Joint inflammation with increase of pro-inflammatory cytokines levels in the synovial fluid might be seen especially when chondromalacia becomes ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…In a 12-month follow-up, the study by Servodio et al conducted on 14 young cases and 17 controls demonstrated a superiority of pulsed electromagnetic fields when combined with a home exercise programme over home exercise alone, showing an effect size of -33.0 (95% CI -45.2 to -20.8) points (31).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In a 12-month follow-up, the study by Servodio et al conducted on 14 young cases and 17 controls demonstrated a superiority of pulsed electromagnetic fields when combined with a home exercise programme over home exercise alone, showing an effect size of -33.0 (95% CI -45.2 to -20.8) points (31).…”
Section: Resultsmentioning
confidence: 98%
“…Two trials compared open kinetic chain exercises with closed ones (25,26). Five studies assessed the effectiveness of different electrical methods (27)(28)(29)(30)(31). Seven trials evaluated the effectiveness of bracing and insoles (19,20,(32)(33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study comparing PEMF associated with a home exercise program to the program alone for patellofemoral pain syndrome showed that in the PEMF group, both function and pain were significantly better at 6 and 12 months [Servodio Iammarrone et al, ]. This was the only other study with electromagnetic fields for patellofemoral pain syndrome found in the literature.…”
Section: Discussionmentioning
confidence: 99%